Timurnesia: Rekonstruksi Identitas Kolektif dan Kedaulatan Kreatif dalam Rimba Algoritmik Musik Indonesia Timur - Muhammad Ilham Mustain Murda; Zandry Aldrin (Universitas Negeri Medan, 2026)
The increasing public attention to Eastern Indonesian music in the digital space has not been fully followed by equal recognition in national music policy, distribution, and industry. This study analyzes Timurnesia as a reconstruction of collective identity and an initial strategy for strengthening the creative richness of Eastern Indonesian music amidst industry centralization and the dominance of digital platforms. The study uses a qualitative approach with a reflective autoethnography method. The primary data comes from the author's field notes as a participant in the Focus Group Discussion